THE RELATIONSHIP BETWEEN THE NARCISSISTIC TENDENCIES AND CYBERBULLYING BEHAVIOR AMONG UNIVERSITY STUDENTS - Permatasari, Nadya Maulidha; Wu, Mingchang (Insight: Jurnal Ilmiah Psikologi, 2021)
The era of globalization promises convenience for humans, with the presence of this information technology tends to affect human civilization. With the existence of electronic media, it can lead individuals towards proposial or anti-social behavior. This study aims to determine the relationship between narcissistic tendencies and cyberbullying behavior among students. The research subjects were 228 students aged 17-21 years. Collecting research data using measuring instruments in the form of the Cyberbullying Scale and Narcissistic Tendency Scale. The data analysis method used is Product Moment. The results of data analysis obtained a correlation value of r = 0.286 and p = 0.000 (p <0.001). The results showed that there was a positive relationship between narcissistic tendencies and cyberbullying behavior among students. This research is expected to help identify and become material for anticipatory considerations regarding cyberbullying behavior in students and be useful for readers, especially adolescents, to be wiser in using social media.